A new robust control using adaptive fuzzy sliding mode control for a DFIG supplied by a 19-level inverter with less number of switches - Benkahla, Mohamed; Taleb, Rachid; Boudjema, Zinelaabidine (НТУ "ХПИ", 2018)
This article presents the powers control of a variable speed wind turbine based on a doubly fed induction generator (DFIG) because of their advantages in terms of economy and control. The considered system consists of a DFIG whose stator is connected directly to the electrical network and its rotor is supplied by a 19-level inverter with less number of switches for minimize the harmonics absorbed by the DFIG, reducing switching frequency, high power electronic applications because of their ability to generate a very good quality of waveforms, and their low voltage stress across the power devices. In order to control independently active and reactive powers provided by the stator side of the DFIG to the grid and ensure high performance and a better execution, three types of robust controllers have been studied and compared in terms of power reference tracking, response to sudden speed variations, sensitivity to perturbations and robustness against machine parameters variations.

В статье описывается управление мощностью ветряной турбины переменной скорости на основе асинхронного генератора двойного питания ввиду их преимуществ с точки зрения экономичности и управления. Рассматриваемая система состоит из асинхронного генератора двойного питания, статор которого подключен непосредственно к электрической сети, а его ротор питается от 19-уровневого инвертора с меньшим количеством коммутаторов для минимизации гармоник, поглощаемых генератором, уменьшая частоту переключения, и устройств силовой электроники вследствие их способности генерировать высокое качество сигналов и низкого уровня напряжения на них. Чтобы независимо управлять активной и реактивной мощностью, подаваемой стороной статора указанного генератора в сеть, и обеспечивать высокую производительность и лучшее конструктивное исполнение, изучены и сопоставлены три типа робастных контроллеров с точки зрения отслеживания мощности, реакции на внезапное изменение скорости, чувствительности к возмущениям и устойчивости к изменениям параметров машины.
Keywords: wind turbine; sliding mode controller; multilevel inverter; rotor side converter; ветряная турбина; контроллер режима скольжения; многоуровневый инвертор